Upravljanje velikih zveri v Sloveniji - Bartol, Matej (Gozdarski vestnik, 2019)
Slovenia has rich experiences with sustainable management and protection of populations of large carnivores; therefore, it is regarded as a model in the field of management of the brown bear, wolf and lynx populations in many places worldwide. In the past, wolf and bear populations in Slovenia were at the brink of extinction, and the lynx was extinct. Presently the lynx is populating Slovenian forests again, and the bear and wolf populations are strengthening (too) quickly in the current decade and have not been in such a favorable condition for a long time. In Slovenia, a polarized opinion in the society represents the greatest danger for the bear and wolf % there are proponents of absolute protection of every single specimen on one hand and proponents of (at least local) extinction of carnivores on the other. This represents a major obstacle for professional management of populations; also out-of-date European environmental legislation has contributed its share to the emergence of such state. Thus, the managers% main challenge should be the updating of the European legislation, with whose help it would be possible to preserve a certain level of tolerance towards the large carnivores with the people living in the areas where they are present and to regulate the numbers of large carnivores in the limits which still enable favorable condition of the populations and are at the same time acceptable for the people who coexist with large carnivores.
Keywords: brown bear; conflicts; cull; Direktiva o habitatih; forest public service; Habitats Directive; javna gozdarska služba; konflikti; large carnivores; management; odstrel; populacija; population; rjavi medved; Slovenia Forest Service; upravljanje; velike zveri; volk; wolf; Zavod za gozdove Slovenije